SIKAP MAHASISWA PENDIDIKAN LUAR SEKOLAH TERHADAP KEGIATAN BADAN EKSEKUTIF MAHASISWA (BEM) FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU PEKANBARU - Ijayani Ijayani; Sumardi Sumardi; Daeng Ayub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to know Student Attitudes of Outside School Education on Student Executive Body Activities (BEM) Faculty of Teacher Training and Education. This research uses descriptive method with quantitative approach. The sample in this study amounted to 54 people, students of PLS force 2015 and 2016 with strata random sampling technique. Data collection techniques used questionnaires. Data analysis techniques use SPSS program, mean and SD calculation, and inferential descriptive analysis. The results of this study indicate that Student Attitudes Out of School Education Activities Student Executive Board (BEM) Faculty of Teacher Training and Education University of Riau Pekanbaru, which is processed through respondents' answers from the questionnaire research. So taken the conclusion that the attitude of out-of-school education on the activities of Student Executive Board (BEM) Faculty of Teacher Training and Education Universitas Riau Pekanbaru pertained good or positive with average mean 3.92. Indicators that contribute most to the Out of School Student Attitudes toward the Student Executive Body (BEM) Activities of Teacher Training and Education Faculty of Riau University of Pekanbaru is affective or emotional indicator of 93.2% in either category or positive. Furthermore, demographic factors of gender and device demography also influence the attitude of out-of-school education students to the activities of Student Executive Board (BEM) Faculty of Teacher Training and Education Universitas Riau Pekanbaru, which is female gender demography with mean 3,99 and male 3,66 big difference is 0.33. While the demographic device, the highest force of the force of 2015 with a mean of 3.99 and force 2016 with 3.86 big mean difference of 0.13.Keywords: Attitude, Activities of Student Executive Board.